Optimalisasi Marketplace Dalam Rangka Meningkatkan Penjualan UKM Luluana Craft Di Era Digital - Andari Andari; Nina Arlofa; Wahyu Oktri Widyarto; Izzudin Fikri Akbar; Muhammad Aqsa Mustafa (Universitas Serang Raya, 2024)
This community service aims to optimize the marketplace in order to increase sales of Luluana Craft Indonesia products, by expanding the market through digital marketing. Based on observations, SMEs have limitations in online marketing, which is only done conventionally. This activity uses a method which is divided into several stages including, pre-activity stage, socialization stage, mentoring stage, and evaluation stage. Implementation of this activity begins with the pre-activity stage, which is the stage of planning material that suits the partner's needs, followed by the delivery of digital marketing, marketplace material, as well as creating accounts on social media and digital platforms, followed by assistance to partners until the partner is able to market their products. by online. The results of this community service show that partners are very enthusiastic about participating in this activity because their understanding of digital marketing has increased. Partners have wider opportunities to market their products, so that apart from increasing sales and other goals, their contribution to handling plastic waste increases.